PHOSPHATE REMOVAL IN LAUNDRY LIQUID WASTE WITH PHYTOREMEDIATION CONSTRUCTED WETLAND SYSTEM USING HYEMALE EQUISETUM AND AZOLLA MICROPHILLA PLANTS - Anggi Munuqy, Wulanda
Laundry wastewater contains Phosphate compounds and other organic materials that are quite high. Various alternative technologies can be used as laundry wastewater treatment, one of which is the constructed wetland system phytoremediation technology. Constructed wetland has two types of irrigation systems, namely Sub surface water systems and Free water surface systems. The main objective of this study is to determine the effectiveness between the two systems in treating laundry industry wastewater and to determine the rate of pollutant removal in both constructed wetland systems so that they can be reused. The constructed wetland reactor was operated in batches using waste from the laundry business. Variations of plant species used are Equisetum hyemale and Azolla microphylla and variations in the amount of phosphate compound load of 7, 5, and 3 ppm. The parameters measured were pH, phosphate and surfactant. The experimental results showed that for the constructed wetland Sub surface flow system with Equisetum hyemale plants can reduce the largest pollutant load to a removal efficiency of 98,8%. While the constructed wetland Free water surface system with Azolla microphylla plants can reduce the largest pollutant load with a removal efficiency of 98.1%. So it can be concluded that phytoremediation constructed wetland Sub surface water system and Free water surface using Equisetum hyemale and Azolla microphylla plants can be used as a laundry wastewater treatment technology.